UFSS 2016 Book of Abstracts - Candice Shoemaker; Eleni Pliakoni; Cary Rivard; Londa Nwadike; Sara Gragg; Judy K. Favor (Urban Food Systems Symposium, 2016)
The 2016 Urban Food Systems Symposium (UFSS), the first of its type, was held to bring together a national and international audience of academic and research-oriented professionals to share and gain knowledge on urban food systems and the role they play in global food security. The symposium included knowledge on: urban agricultural production, local food systems distribution, urban farmer education, urban agriculture policy, planning and development, food access and justice, and food sovereignty. The abstract book includes the invited speakers and the contributed oral and poster speakers for the 2016 UFSS.
Keywords: symposium; urban food systems